Analysis of the Effect of Service Quality and Product Quality on Customer Satisfaction and Customer Loyalty using the Path Analysis Method (Case Study of KFC Taman Harapan Indah Bekasi) Loyalitas Pelanggan dengan Metode Analisis Jalur (Studi Kasus KFC Taman Harapan Indah Bekasi) - Vendhi Prasmoro, Alloysius (Journal of Industrial and Engineering System, 2024)
This research investigates the impact of product and service quality on customer satisfaction and loyalty in the competitive fast-food market of Bekasi. Based on customer survey data in 2022, customer satisfaction at 92.9%, where this figure is still below the minimum figure that must be achieved, namely 98%. The study utilizes path analysis to analyze the relationship between the independent variables, product quality, and service quality, and the dependent variables, customer satisfaction, and customer loyalty. Additionally, to propose improvements to boost customer satisfaction and loyalty. Employing an explanatory research approach, the study involves a sample of 100 respondents who have conducted transactions at KFC Taman Harapan Indah Bekasi at least twice. The path analysis reveals that both product quality and service quality significantly influence customer satisfaction and loyalty. However, customer satisfaction does not have a significant effect on loyalty. Moreover, the study finds that indirect effects through customer satisfaction are smaller than the direct effects. Based on customer complaint analysis, the prioritized quality improvements to enhance customer satisfaction and loyalty include implementing more effective marketing strategies, conducting employee training and development, and optimizing staffing through increased personnel or improved scheduling